The use of the international phonetic alphabet as a tool to develop a standard pronunciation in basic level students - Deras Navas, Silvia Carolina; López Cornejo, Patricia del Carmen; Ramos López, Mauricio (2024)
All along history, different cultures have emerged; everyone has developed their own code and ways of communication to supply different needs. This need of communication has allowed each community to develop and better an own language throughout the time. English is a worldwide spread language that attracts more learners everyday. Surely for the speech of a non-native speaker of English to flow and be understood, the teaching-learning process of that language must be accurate and effective. In order to make this process less frustrating and confusing and at the same time accurate and effective so an interlocutor that speaks the language can process and understand what the non-native speaker says, a variety of techniques and tools shall be used by teachers and learners throughout the whole process.